2020
DOI: 10.1186/s12967-020-02266-3
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note to: Stromal vascular fraction cells for the treatment of critical limb ischemia: a pilot study

Abstract: The Editor-in-Chief and the publisher have retracted this article [1]. An investigation by the Lithuanian Bioethics Committee concluded that, contrary to the statements in the article, the study described was not conducted in the Vilnius City Clinical Hospital and the Commission of Medical Ethics did not issue any approval for such a study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The study by Darinskas et al included 15 patients with rest pain and some with ulcerations; SVF was injected once or twice in the ischemic limb along the arteries (150). Clinical improvement in terms of pain, meters of claudication and ABI occurred in 86.7% of patients, but only 6 patients out of 15 had ulcers and two patients underwent major amputation, although the amputation sites healed completely.…”
Section: Clinical Trials In No-option Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Darinskas et al included 15 patients with rest pain and some with ulcerations; SVF was injected once or twice in the ischemic limb along the arteries (150). Clinical improvement in terms of pain, meters of claudication and ABI occurred in 86.7% of patients, but only 6 patients out of 15 had ulcers and two patients underwent major amputation, although the amputation sites healed completely.…”
Section: Clinical Trials In No-option Patientsmentioning
confidence: 99%
“…Clinical improvement in terms of pain, meters of claudication and ABI occurred in 86.7% of patients, but only 6 patients out of 15 had ulcers and two patients underwent major amputation, although the amputation sites healed completely. Moreover, the vascular collateral network formation of arteries was observed by digital subtraction angiography upon SVF cell therapy (150).…”
Section: Clinical Trials In No-option Patientsmentioning
confidence: 99%
“…Adipose tissuederived stromal vascular fraction (SVF) contains a variety of cells, including mesenchymal stem cells (MSCs), which is a promising therapeutic option for OA. With the application of conventional liposuction and isolation methods, SVF in adipose and connective tissues can be easily obtained from patients [10]. Michalek et al showed significant improvement in OA symptoms, particularly pain reduction and decrease in nonsteroidal anti-inflammatory drug usage in a large group of 1,128 patients with OA [11].…”
Section: Introductionmentioning
confidence: 99%